PENAFSIRAN STRUKTUR BAWAH PERMUKAAN DAERAH BANGKA UTARA, BERDASARKAN ANOMALI GAYA BERAT - W. H.Simamora (Jurnal Geologi dan Sumberdaya Mineral, 2007)
The gravity measurement carried out in the North Bangka Quadrangle has produced 1:250,000 Bouguer anomaly, regional and residual gravity maps. Bouguer anomaly values range from 5.0 to 39.0 mgal, regional anomalies arebetween 13.0 until 35.0 mgal and residual anomalies are from -7.0 to 10.0 mgal. The Bouguer anomalies aredivided into three types, i.e : low, medium and high, while the residual anomaly is categorized as positive and negativeareas.The modelling result of three sections of residual anomaly shows that the density of 2.69 gr/cc and interpreted asPemali Complex belongs to the basement in the area. This basement is Pemali Complex which is intruded by rocks with densities of 2.54 ; 2.56 and 2.58 gr/cc and indicated as granitic intrusion. Boundary between Pemali complex, Tanjunggenting formation and granitic intrusion is fault contact. This contact could be potential for secondary tin deposit resulted from weathered granite.Â Keywords : gravity, residual anomaly, density, tin deposit, Bangka